HPV genotyping agreement between paired cervical cytological sample and biopsy across lesion severity and vaccination - Shimin Chen; Qiaoyun Du; Jian Yin; Xiaoqian Xu; Wen Chen; Qinjing Pan; Xun Zhang; Ying Hong; Wenhua Zhang; Bin Liu; Jianfeng Cui; Shangying Hu; et al. (Virology Journal)
Abstract Background Cytological samples are genotyped to inform clinical management of HPV-infected women due to their accessibility. Conversely, HPV genotypes identified in biopsies are deemed directly associated with cervical lesions. Thus, investigating genotyping agreement between these two sample types and potential influence of lesion severity and vaccination status on their degree of concordance is essential for understanding their diagnostic reliability. Methods Paired cervical cytological samples and formalin-fixed paraffin-embedded (FFPE) biopsies from 392 cervical intraepithelial neoplasia or cancer (CIN+) cases (187 CIN1, 111 CIN2, 94 CIN3+; 262 unvaccinated, 130 vaccinated) were genotyped using SPF10-DEIA-LiPA25 detection system. Strength of agreement was measured by kappa, with thresholds indicating varying levels of agreement. Results Overall, most HPV genotypes were more frequently detected in cytological samples, with seven genotypes showing statistical differences between sample types (HPV39, 51, 52, 53, 56, 58, 68/73). Multi-type infection was more prevalent in cytological samples (147 versus 76, P McNemar’s test<0.001), whereas single-type infection was more common in FFPE biopsies (233 versus 296, P McNemar’s test<0.001). Proportions of observed agreement for all genotypes detected exceeded 95% and Prevalence-And-Bias-Adjusted kappa values (range: 0.832 to 0.990) indicated “Strong” (threshold: 0.80 to 0.90) to “Almost Perfect” (threshold: above 0.90) agreement. Lesion severity and vaccination status had negligible impacts on genotyping agreement. Conclusions In conclusion, HPV genotyping by cytological samples and FFPE biopsies performed equally well regardless of lesion severity and vaccination status, directly supporting reliable utility of cytological HPV genotyping for clinical decisions. However, impact of sample type needs to be considered when interpretating and utilizing multi-type and/or single-type infection for scientific research. Trial registration ClinicalTrials.gov (NCT00779766). Registered on the 23th of October 2008.